Cloud computing and service sScience : 7th International Conference, CLOSER 2017, Porto, Portugal, April 24-26, 2017, Revised selected papers /: 7th International Conference, CLOSER 2017, Porto, Portugal, April 24-26, 2017, Revised selected papers. (2018) - Unknown
No abstract available